2021
DOI: 10.1038/s41467-021-23426-z
|View full text |Cite
|
Sign up to set email alerts
|

Sulfur stabilizing metal nanoclusters on carbon at high temperatures

Abstract: Supported metal nanoclusters consisting of several dozen atoms are highly attractive for heterogeneous catalysis with unique catalytic properties. However, the metal nanocluster catalysts face the challenges of thermal sintering and consequent deactivation owing to the loss of metal surface areas particularly in the applications of high-temperature reactions. Here, we report that sulfur—a documented poison reagent for metal catalysts—when doped in a carbon matrix can stabilize ~1 nanometer metal nanoclusters (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
87
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 147 publications
(89 citation statements)
references
References 49 publications
2
87
0
Order By: Relevance
“…These results imply that the EMSI-dependent electronic structure changes of Pt single atom may play a determinant role in the catalysis. , DFT simulations uncovered that the electron enrichment on PtNC/S–C could optimize the H* binding energy on Pt and promote the decrease of Δ G H (Figure g). Besides, we also found that the enrichment of electrons over the Pt cluster can tune the selectivity of propane dehydrogenation and promote the catalytic selectivity to propene …”
Section: The Influence Of Metal Properties On Emsimentioning
confidence: 78%
See 1 more Smart Citation
“…These results imply that the EMSI-dependent electronic structure changes of Pt single atom may play a determinant role in the catalysis. , DFT simulations uncovered that the electron enrichment on PtNC/S–C could optimize the H* binding energy on Pt and promote the decrease of Δ G H (Figure g). Besides, we also found that the enrichment of electrons over the Pt cluster can tune the selectivity of propane dehydrogenation and promote the catalytic selectivity to propene …”
Section: The Influence Of Metal Properties On Emsimentioning
confidence: 78%
“…Besides, we also found that the enrichment of electrons over the Pt cluster can tune the selectivity of propane dehydrogenation and promote the catalytic selectivity to propene. 43 Chen et.al reported a nitrogen-doped graphene-supported Ir single atom catalyst for ORR, in which the particle size effect induced change of EMSI was also involved. 38 They found that electrons transferred from a single Ir atom to the nearby N atoms in Ir−N 4 structure, while the Ir 19 cluster preserved the metallic state (see Figures 5h and 5i).…”
Section: The Influence Of Metal Properties On Emsimentioning
confidence: 99%
“…In addition to nitrogen, sulfur is also used to fix and modify metals [5,48,58,59] . As shown in Table 2, the most common functions of S are to form metal–S species, [5,48,58,59,108] regulate the electronic state of metals, [5,58,74,108,109] and enhance their dispersion and stability [5,58,59,74,108,109] .…”
Section: Metal Catalyst Anchored By Heteroatomsmentioning
confidence: 99%
“…[5,48,58,59] As shown in Table 2, the most common functions of S are to form metal-S species, [5,48,58,59,108] regulate the electronic state of metals, [5,58,74,108,109] and enhance their dispersion and stability. [5,58,59,74,108,109] In addition, the interaction between metal and S can also change the reduction state of metal [108] and adjust the ability of metal to adsorb and desorb substrate/intermediate, [58,74] so as to optimize the efficiency of catalytic reaction. Liang and co-workers successfully prepared Sdoped carbon stabilized Pt nanoclusters (Pt/SÀ C).…”
Section: Metal Catalysts Anchored By S B and Pmentioning
confidence: 99%
See 1 more Smart Citation